Khutbae śikaśikayyaha - Nadavī, Ahamada Jaapharī (Alamadāra Buka Ḍīpo, 1911)
Article on Nahj al-balāghah, Islamic politico-legal treatise, variously attributed to ʻAli ibn Abī Tālib, Caliph, 600 (ca.)-661, and Muḥammad ibn al-Ḥusayn Sharīf al-Raḍī, 969 or 70-1016.